La ética en inteligencia artificial desde la perspectiva del derecho (2021)
This article is the product of a study that aims to demonstrate the relevance of ethics in the development of artificial intelligence, for which it will present an exploration of the positions of experts and different international organizations, including the European Union, which coincide in establishing similar paradigms on the potential scope of the autonomy of AI as a being endowed with cognitive capacity or intelligence, but not with conscience or reason, so the right to freedom plays a transcendental role in defining the category of AI as an individual. In order to bring the reader closer to the object of study, the objectives and categories of the conceptualization of the purposes of AI, the confrontation between autonomy and automation and intelligence and reasoning, will be presented, so that the reader can make a critical analysis that allows him to have his own position on the generation of legal responsibilities of the AI as a legal person and its programmers. Similarly, issues such as transhumanism, understood as a mechanism to improve human life and performance, bioethics, which should be based on respect for human dignity and the protection of fundamental rights, will be addressed, to finally, specify the positions of experts and the European Commission on the adaptation of the Charter of Fundamental Rights to achieve a reliable and ethical AI.